2006
DOI: 10.1890/0012-9658(2006)87[1411:eeont]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of Neutral Theory

Abstract: We describe a general framework for testing neutral theory. We summarize similarities and differences between ten different versions of neutral theory. Two central predictions of neutral theory are that species abundance distributions will follow a zero-sum multinomial distribution and that community composition will change over space due to dispersal limitation. We review all published empirical tests of neutral theory. With the exception of one type of test, all tests fail to support neutral theory. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
348
2
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(362 citation statements)
references
References 77 publications
(120 reference statements)
3
348
2
9
Order By: Relevance
“…Equilibrium is an important part of UNTB, and the probable lack of equilibrium has been used to criticize UNTB or show that predictions are inconsistent given time and other factors [22,73]. However, we point out that many community studies are consistent with UNTB and that although equilibrium may not have been demonstrated in all cases, it is likely that some relaxation of this constraint and the zero-sum assumption is permitted [74,75] or is unnecessary to predict SAD [76,77].…”
Section: Discussionmentioning
confidence: 84%
“…Equilibrium is an important part of UNTB, and the probable lack of equilibrium has been used to criticize UNTB or show that predictions are inconsistent given time and other factors [22,73]. However, we point out that many community studies are consistent with UNTB and that although equilibrium may not have been demonstrated in all cases, it is likely that some relaxation of this constraint and the zero-sum assumption is permitted [74,75] or is unnecessary to predict SAD [76,77].…”
Section: Discussionmentioning
confidence: 84%
“…The neutral model, due largely to its assumption of ecological equivalency among species within a community, has generated a great deal of controversy (for recent examples see Holyoak and Loreau, 2006;McGill et al, 2006;Alonso et al, 2006). There are differences of ecological significance between tintinnid species, for example LOD is related to the size of prey most efficiently grazed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, just as selection nonrandomly alters the relative abundance of alleles, ecological filtering may fall more strongly upon individuals of some species than upon others, thus driving a community toward niche assembly. Accordingly, communities subject to intense predation or disturbance regimes appear resistant to stochasticity in community structure, and are well fitted by nicheassembly models (McGill 2003;McGill et al 2006;Chase 2007). On the other hand, communities subject to relatively benign environments and moderate rates of predation and disturbance appear more sensitive to stochasticity, and are well fitted by models of dispersal assembly (Fukami 2004).…”
Section: Richness Experimentsmentioning
confidence: 99%